Recent Advances and Future Prospects of Molecular Imprinting Polymers as a Recognition Sensing System for Food Analysis: A Review - Almajed Asaad Abdullah Sfoog; Norlaili Abu Bakar; Nurulsaidah Abdul Rahim; Wan Rusmawati Wan Mahamod; Norhayati Hashim; Siti Kamilah Che Soh (Indonesian Journal of Chemistry, 2022)
Molecular imprinting polymers (MIPs) have been widely used to produce stable polymeric materials due to their highly selective binding sites to determine the analyte (target molecule) in food products. MIPs begin with a complex compound between the template molecule and the functional monomers that can be polymerized when there is a closely crossed link. MIPs left specific cavities after the removal of templates during washing, which complements the size and shape of the templates. The use of MIPs has contributed to novel advances in materials science, polymer science, natural science, and other multi-disciplinary systems. Optical chemical sensor is an exciting field in MIPs today due to comprehend the unique affirmation limit of associated polymers giving stable polymers with high molecular recognition capabilities. MIPs display a wide extent of relevance, incredible flexibility, security, and high selectivity; their internal affirmation districts can be explicitly gotten together with design molecules to achieve specific affirmation. This review covers the various achievements of sensors used in laboratory analyses. The advancement in the development of MIPs is evaluated with an accentuation on the preparation principle, the discovery process, the molecular recognition mechanism and future perspectives and challenges for MIPs in building an optical chemical sensor.